Tissue engineering in periodontal regeneration: A brief review - Sarita Dabra; Kamalpreet Chhina; Nitin Soni; Rakhi Bhatnagar (Wolters Kluwer Medknow Publications, 2012)
Periodontal disease is a major public health issue and the development of effective therapies to treat the disease and regenerate periodontal tissue is an important goal of today's medicine. Regeneration of periodontal tissue is perhaps one of the most complex process to occur in the body. Langer and colleagues proposed tissue engineering as a possible technique for regenerating the lost periodontal tissues. Tissue engineering is a multidisciplinary field, which involves the application of the principles and methods of engineering and life sciences to help in the development of biological substitutes to restore, maintain or improve the function of damaged tissues and organs. A Google/Medline search was conducted and relevant literature evaluating the potential role of the tissue engineering in periodontal regeneration, which included histological studies and controlled clinical trials, was reviewed. A comprehensive search was designed. The articles were independently screened for eligibility. Articles with authentic controls and proper randomization and pertaining specifically to their role in periodontal regeneration were included. The available literature was analyzed and compiled. The analysis indicate tissue engineering to be a promising, as well as an effective novel approach to reconstruct and engineer the periodontal apparatus. Here, we represent several articles, as well as recent texts that make up a special and an in-depth review on the subject. The purpose behind writing this brief review has been to integrate the evidence of research related to tissue engineering so as to implement them in our daily practice.